Climate-Smart Agriculture in Southeast Asia: Performance, Adoption Realities, and a Practical Way Forward (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Southeast Asia is battered by intensifying climate hazards, yet the region continues to feed hundreds of millions through its vast rice bowls. Climate-Smart Agriculture (CSA) is increasingly regarded as the most viable route to sustain production, slash greenhouse-gas emissions, and strengthen farmer resilience in the face of worsening shocks. This systematic review consolidates the strongest field-based evidence currently available across the region. Methane emissions are reduced by approximately 35 % and global warming potential by 29 % when Alternate Wetting and Drying (AWD) is correctly applied, while irrigation water use drops substantially and rice yields remain stable or increase modestly. Greenhouse-gas fluxes are suppressed by roughly 20 % through biochar incorporation, and crop productivity is raised between 10 % and 28 %, with the most pronounced benefits observed on the acidic, low-fertility soils that dominate mainland and insular Southeast Asia. In the Lower Mekong Basin, the System of Rice Intensification (SRI) has been shown to deliver average yield gains of 52 % alongside 70 % higher net economic returns. Despite these robust outcomes, widespread uptake is still constrained by multiple barriers. Training is often inadequate, initial investment costs are perceived as prohibitive, and access to land, credit, extension services, and timely information is distributed unequall-particularly disadvantaging women farmers. Large evidence gaps persist for non-rice agroecosystems and for standardised, comparable indicators of resilience. The review therefore concludes with a clearly sequenced research and policy agenda aimed at shifting CSA from scattered demonstration plots to landscape-scale transformation across Southeast Asia’s diverse farming systems.
Keywords: Climate-smart agriculture; Adoption constraints; Resilience measurement; Alternate wetting and drying; Rice intensification